Validating and Identifying Health and Safety Performance Improvement Indicators: Experience of Using Delphi Technique - Agumba, Justus N. (Journal of Economics and Behavioral Studies, 2015)
The literature on health and safety (H&S) is bound with different elements and indicators of measuring H&S performance. The purpose of this paper is to discuss the success and challenges of using quantitative and qualitative approach of Delphi technique in validating and identifying H&S performance indicators that small and medium construction enterprises (SMEs) can use to measure and monitor their H&S performance improvement at project level. Furthermore, discuss the identification of experts in the field of H&S, ways of improving consensus analysis and minimizing experts’ non-response. This study is based on practical experience of the researchers pertaining to the Delphi technique method which is a constructivist or interpretive approach to knowledge. The study started with an extensive literature review to identify core elements and leading indicators characterizing H&S culture to develop a Delphi questionnaire that was used in the first round of Delphi. A four round Delphi technique was conducted to attain consensus of the identified H&S indicators. The experts were identified from published articles of H&S, practitioners’ website of H&S and word of mouth. The use of email was used as a mode of communication. This study set to warn but also encourage the use of Delphi technique as a method to unearth information in areas where consensus has not been reached such as H&S performance measurement indicators for construction SMEs in South Africa.